Eales’ Disease: A Successful Treatment with Oral Corticosteroid - Alma Pustika Kartikananda Retina Fibularis; Halida Wibawaty (Universitas Airlangga, 2023)
Introduction: Eales’ disease is an idiopathic inflammatory venous occlusion primarily affecting the peripheral retina. It commonly affects healthy young men aged 20-30 years, and 50-90% of patients develop bilateral involvement. Retinal changes include perivascular phlebitis, peripheral nonperfusion, and neovascularization. Case Presentation: We present a case of bilateral Eales’ disease; a 38-year-old man presented to our hospital with chief complaints of decreased and blurred vision, photopsia, and floaters in both eyes. The best corrected visual acuity (BCVA) at the initial presentation was hand movement in the right eye (RE) and 0.3 in the left eye (LE). The anterior segment and intraocular pressure (IOP) were normal. Funduscopy of both eyes highlighted dense vitreous opacity. In the RE, we found perivascular sheathing, perivascular exudates, dot and flame shape intraretinal hemorrhages, and focal occlusion of retinal vessels. In the LE, we found perivascular sheathing, perivascular exudates, and dot and flame shape intraretinal hemorrhages. Initial optical coherence tomography (OCT) results show central macular thinning. The disease resolved rapidly with an oral corticosteroid before the patient underwent pars plana vitrectomy. Conclusions: Eales’ disease can be treated with corticosteroids, anti-VEGF, laser photocoagulation, and pars plana vitrectomy. Even though the patient was planned for pars plana vitrectomy, we tried initial therapy using oral corticosteroids, which responded well to the patient’s chief complaints. OCT results also showed improvement in macular thickness after the third follow-up. Oral corticosteroid therapy shows good results in Eales’ disease treatment.